Exploring the Use of Manual Liquid Based Cytology, Cell Block with Immunomarkers p16/ki67, VIA and HPV DNA Testing as a Strategy for Cervical Cancer Screening in LMIC: A Prospective Study - Manoli, Nandini Nandish; Devegowda, Devananda; Varshini, Ashoka; Ramesh, Pushkal Sinduvadi; Mathew, Sherin Susheel; Manoli, Nandish Siddappa (Recent Developments in Medicine and Medical Research Vol. 1, 2021)
Among low- and middle-income countries (LMIC), cervical cancer is the fourth most common malignancy in women. Cervical cancer is detected using a variety of approaches, including the conventional Pap smear (CPS), Liquid Based Cytology, and supplementary techniques such as Cell Block with immunocytochemistry. Another approach being promoted as a key screening tool is the VIA. HPV DNA testing and other molecular diagnostics have been at the forefront of screening efforts. All of the above methods were used in this study by using cost-effective in-house procedures to see if they could be useful in clinical settings. We found them valuable in light of the need for greater work and people training in order to improve cervical cancer diagnosis. There is a need for a uniform policy of screening of women at the primary health care center level with increasing the awareness of the different methods among the public.